The Application of Wearable Glucose Sensors in Point-of-Care Testing - Zhang, Sheng; Zeng, Junyan; Wang, Chunge; Feng, Luying; Song, Zening; Zhao, Wenjie; Wang, Qianqian; Liu, Chen (Frontiers in Bioengineering and Biotechnology, 2021)
Diabetes and its complications have become a worldwide concern that influences human health negatively and even leads to death. The real-time and convenient glucose detection in biofluids is urgently needed. Traditional glucose testing is detecting glucose in blood and is invasive, which cannot be continuous and results in discomfort for the users. Consequently, wearable glucose sensors toward continuous point-of-care glucose testing in biofluids have attracted great attention, and the trend of glucose testing is from invasive to non-invasive. In this review, the wearable point-of-care glucose sensors for the detection of different biofluids including blood, sweat, saliva, tears, and interstitial fluid are discussed, and the future trend of development is prospected.